The active metabolites of Eucommia ulmoides leaves alleviate atherosclerosis induced by a high-fat diet and VD3 in rats - Gong, Man; Zhu, Lili; Cui, Bingdi; Ling, Cong; Liu, Xiaoqian; Wang, Zhimin; Dai, Liping (Frontiers in Pharmacology, 2025)
BackgroundAtherosclerosis (AS) is a prevalent systemic disease, with its morbidity and mortality rates escalating globally. Traditional Chinese medicine (TCM), characterized by its multi-pathway and multi-target approach, offers distinct advantages in the diagnosis and treatment of atherosclerosis. Eucommia ulmoides (E. ulmoides) leaves, known for their medicinal and nutritional benefits, exhibit multi-targeted mechanisms against AS, although their precise pharmacological basis and molecular mechanisms are not fully understood. In this study, two active metabolites were isolated from the leaves of E. ulmoides leaves. Preliminary pharmacodynamic evaluation demonstrated that one metabolite, referred to as Eucommia ulmoides leaves (EUL 50), exhibited superior efficacy. This research focuses on the effects of EUL 50 on AS.MethodsThe study assessed the impact of EUL 50 supplementation on AS in male Wistar rats, which were administered EUL 50 at doses of 70 mg/kg (low) and 140 mg/kg (high) to evaluate effects on lipid metabolism, NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activity, and autophagy. Additionally, the effect of EUL 50 on NLRP3 inflammasomes and autophagy was examined in an oxidized low-density lipoprotein (ox-LDL)-induced THP-1 foam cell model.ResultsEUL 50 significantly reduced serum inflammation markers, including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), vascular cell adhesion molecule-1 (VCAM-1), intercellular cell adhesion molecule-1 (ICAM-1), and matrix metalloproteinase-9 (MMP-9). It also lowered the levels of triglycerides (TGs), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) in the blood while increasing high-density lipoprotein cholesterol (HDL-C) levels in AS rats. Histopathological analysis of liver tissue, along with liver Oil Red O staining and aortic hematoxylin and eosin (HE) results, indicated that EUL 50 improved lipid accumulation. Furthermore, EUL 50 inhibited ox-LDL-induced foam cell formation and cholesterol (TC) accumulation while also suppressing the levels of TNF-α, IL-6, and IL-1β. Additionally, EUL 50 inhibited the expressions of NLRP3, ASC, caspase-1, and p62 proteins in AS rats and foam cells, thereby hindering the progression of AS.ConclusionEUL 50, an active metabolite from E. ulmoides leaves, demonstrates potential in preventing and treating AS through autophagy-mediated regulation of NLRP3 inflammasomes. These findings support the potential development of health products derived from E. ulmoides leaves.